Fish gathering lamp system and fishing device
By combining laser light sources and fluorescence conversion systems, blue light is converted into yellow-green light by using Ce:LuAG fluorescent ceramics, which solves the problem of low luminescence efficiency of traditional LED fish lamps, and realizes a high-brightness and low-power light source, and improves the fish luring effect underwater.
Patent Information
- Application Number
- CN202411872476.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
Traditional LED fish lamps have low luminous efficiency, difficulty in dissipating heat, and limited light propagation capabilities, making it difficult to effectively lure fish underwater.
A fish lamp system combining a laser light source and a fluorescence conversion system is used to excite Ce:LuAG fluorescent ceramics through blue light, converting them into yellow-green light, improving the photoelectric conversion efficiency.
It realizes a high-brightness and low-power light source, effectively reducing the impact of waste heat on the equipment, extends the service life, and improves the fish luring effect underwater.
Smart Images

Figure CN119687405A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fishery and fishing, and in particular relates to a fish gathering lamp system and a fishing device. Background Art
[0002] Fish attracting lights are widely used in fisheries to attract fish. Common fish attracting lights mostly use high-brightness LED chips, but traditional LED chips have low luminous efficiency, difficulty in heat dissipation, and limited light transmission capabilities, making it difficult to achieve the ideal fish attracting effect underwater.
[0003] Therefore, in view of the above technical problems, it is necessary to provide a fish gathering lamp system and a fishing device.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0005] The object of the present invention is to provide a fish attracting lamp system and a fishing device.
[0006] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0007] The fish attracting lamp system includes a laser light source and a matching optical fiber system for transmitting the laser, and also includes a fluorescence conversion system for receiving blue laser. The fluorescence conversion system includes
[0008] The fluorescent ceramic structure is arranged far away from the laser light source and is used to emit yellow-green light after being irradiated by the laser.
[0009] In one or more embodiments of the present invention, the phosphor ceramic structure includes a main structure of Ce:LuAG phosphor ceramic.
[0010] In one or more embodiments of the present invention, Ce:LuAG fluorescent ceramics 3+ The doping amount is 0-9.9wt.%.
[0011] In one or more embodiments of the present invention, the main structure includes a cylindrical thread structure or an inclined cross-section thread structure.
[0012] In one or more embodiments of the present invention, the doping of Ce:LuAG in the Ce:LuAG fluorescent ceramic is uniform doping or gradient doping.
[0013] Regarding the setting of gradient doping, the doping concentration formula is a=ε·c, where a: represents the absorption coefficient, ε: represents the molar absorption coefficient, which is mainly related to the absorption wavelength range. This invention patent uses 450nm blue light irradiation, and the molar absorption coefficient is between 2000-4000L·moL -1 cm -1 The absorption coefficient of uniform doping is 0.8, and the doping concentration is 0.0002-0.0004 mol / L. The absorption coefficient of the first section of gradient doping is 0.11 cm -1 , the corresponding concentration range is 2.75×10 -5 mol / L-5.5×10 -5 mol / L, the absorption coefficient of the second segment is 0.14cm -1 , the corresponding concentration range is 3.5×10 -5 mol / L-7.0×10 -5 mol / L, the absorption coefficient of the third segment is 0.202cm -1 , the corresponding concentration range is 5.05×10 -5 mol / L-1.01×10 -4 mol / L, the absorption coefficient of the fourth segment is 0.346cm -1 , the corresponding concentration range is 8.65×10 -5 mol / L-1.73×10 -4 mol / L, the absorption coefficient of the fifth segment is 0.69cm -1 , the corresponding concentration range is 1.725×10 -4 mol / L-3.45×10 -4 mol / L
[0014] In one or more embodiments of the present invention, the length of the main structure satisfies: I(x) = I0e -ax In this formula, I0 represents the intensity of the incident light, a represents the absorption coefficient, x represents the geometric distance traveled by the light in the fluorescent ceramic rod, and I(x) represents the remaining light intensity after x geometric distance.
[0015] In one or more embodiments of the present invention, Ce:LuAG fluorescent ceramics are Ce 3+ The dopant concentration ranges from 0 to 9.9 wt.% and is mixed with oxide powder, pressed into shape, and then dried and sintered to obtain the product. The oxide is Al2O3 nanopowder, and the average particle size of the nanopowder is 20 to 25 nm. The ball milling medium is alumina balls with a diameter of 1 to 3 mm. The ball milling time is 24 hours, the rotation speed is 200 rpm, the solvent is ethanol or acetone, the solvent and solid ratio is 2:1, and the ball milling temperature is set to room temperature.
[0016] In one or more embodiments of the present invention, the oxide powder is selected from: aluminum oxide powder Al2O3, lutetium oxide Lu2O3, cerium oxide CeO2.
[0017] In one or more embodiments of the present invention, the sintering is performed at a temperature between 1700° and 1800° for 10-20 hours.
[0018] In one or more embodiments of the present invention, annealing treatment is further performed after sintering: at a temperature of 800°-1200° for 4-8 hours.
[0019] In one or more embodiments of the present invention, a fishing device includes a fish attracting light system.
[0020] Compared with the prior art, the fish attracting lamp system and fishing device of the present invention emits blue laser light through the blue light LD chip to excite the doped Ce: LuAG fluorescent ceramic, converting the blue light into yellow-green light suitable for attracting fish, with high photoelectric conversion efficiency, and can provide a high-brightness light source with low power consumption.
[0021] Through remote excitation, the blue light LD chip and the doped Ce:LuAG fluorescent ceramics are packaged separately, and the heat dissipation is managed separately, which effectively reduces the impact of waste heat on the blue light LD chip and the doped Ce:LuAG fluorescent ceramics, and extends the service life of the blue light LD chip and the doped Ce:LuAG fluorescent ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A schematic diagram of the system composition structure of a fish attracting lamp system in one embodiment of the present invention;
[0024] Figure 2 FIG. 4 is a schematic diagram of the structure of a fluorescence conversion system in one embodiment of the present invention.
[0025] Description of main reference numerals:
[0026] 1. FC fiber connector, 2. Anti-collision cage, 3. FC fiber coupler, 4. Fluorescent ceramic rod, 5. Fixer, 6. Loose-leaf. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0028] The laser fish attracting lamp system using Ce:LUAG fluorescent conversion material includes: a laser lighting system, a 10-1000mm transmission optical fiber, and a fluorescent conversion system. The laser optical fiber system is provided with a laser outlet, the coupler has a light inlet and a light outlet, and the fluorescent conversion system has a light inlet; the laser outlet of the laser lighting system is docked with the light access port of the coupler, the 10-1000mm transmission optical fiber is docked with the light outlet of the coupler, the other end of the optical fiber is docked with the FC connector at the light inlet of the fluorescent conversion system, the FC connector is docked with the FC optical fiber coupler, and the fluorescent ceramic rod is docked with the light outlet of the FC optical fiber coupler through a thread; the laser lighting system can emit a blue laser light source, which enters the optical fiber through the coupler and is transmitted to the fluorescent conversion system. Furthermore, the 10-1000mm transmission optical fiber can also be provided with a winder. The laser lighting system has a wire access end that can be connected to an external power supply; the external power supply can adjust the power of the laser brightness emitted by the laser lighting system, and the power is adjusted by controlling the current size of the external power supply. The fluorescent conversion system includes: an anti-collision cage, a fixture, an FC optical fiber coupler, and a rod-shaped fluorescent ceramic.
[0029] There is a raised cylindrical channel on the anti-collision cage, and the fixture is welded on the other side of the raised cylindrical channel. There is a fixing frame inside the anti-collision cage; there is an optical access port on the left side of the connector, and there is an FC connector at the optical access port to fix the optical fiber. After fixation, the FC connector is docked with the FC fiber coupler, and there is a threaded light outlet on the right side of the FC fiber coupler; a threaded docking port is provided at one end of the rod-shaped fluorescent ceramic.
[0030] The raised cylindrical channel on the anti-collision cage has a fixture welded on the channel, one end of which serves as the entrance for the 10-1000mm optical fiber and the other as the fixing point for the FC optical fiber coupler.
[0031] One end of the fixture is welded to one side of the protruding cylindrical channel, and the other side of the fixture fixes the FC optical fiber coupler at a position in the same straight line as the hollow cylinder.
[0032] The raised cylindrical channel is a hollow cylinder; the 10-1000mm optical fiber enters the anti-collision cage through the hollow cylinder and connects with the FC connector on the other side of the hollow cylinder, and the FC connector and the light inlet of the FC fiber coupler are connected; thereby, the 440nm-460nm blue light laser emitted by the laser illumination system is irradiated into the FC fiber coupler of the anti-collision cage.
[0033] There is a groove thread on the right side of the FC fiber coupler, and there is also a connecting thread on one side of the rod-shaped fluorescent ceramic that has been processed. After the threads are connected, the 440nm-460nm laser inside the connector is incident on the inside of the rod-shaped fluorescent ceramic through the threaded light outlet.
[0034] By grinding the rod-shaped fluorescent ceramic, cylindrical threads and inclined cross-section threads appear.
[0035] The cylindrical thread corresponds to a direct-type fish attracting lamp, and the laser is directly emitted into the fluorescent conversion material doped with 0-9.9% Ce:LuAG through the connector thread light outlet.
[0036] The inclined cross-section thread corresponds to the reflective fish attracting lamp. The laser is incident on the inclined cross-section through the connector thread light outlet, and then enters the fluorescent conversion material through the refraction of light. According to the law of refraction: n1sinθ1=n2sinθ2, it can be seen that the section angle is related to the refractive index of the incident surface medium. The section angle range is 0-arctan (1.33 / 1.256), and the refractive index range is 0-1.33.
[0037] Rod-shaped fluorescent ceramics can use uniform doping and gradient doping.
[0038] The length of the ceramic rod uniformly doped with Ce: LuAG fluorescent conversion material is selected according to the Lambert-Beer law:
[0039] I(x)=I0e -ax .
[0040] Ce in Gradient Doped Ce:LuAG Fluorescence Conversion Material Ceramic Rod 3+ The doping concentration is also determined according to the Lambert-Beer law. At this time, the specific length of each section of the fluorescent ceramic rod is limited to 2 cm, and the total length of the ceramic rod is 10 cm. Gradient doping can effectively improve the optical efficiency, make the heat distribution uniform, enhance the stability and service life of the device, and is suitable for high-power laser light sources.
[0041] The high-power laser fish attracting lamp provided by the present invention includes a laser lighting system, a coupler, a 0-1000mm optical fiber and a fluorescence conversion system. The laser lighting system is provided with a light outlet, the coupler has a light inlet and a light outlet, the 10-1000mm optical fiber has a winder, the fluorescence conversion system has a light inlet, and there is an FC connector at the light inlet. The laser light outlet is docked with the light inlet of the coupler, the light outlet of the coupler is docked with the optical fiber, the other end of the optical fiber is docked with the FC connector of the light inlet of the fluorescence conversion system, the FC connector is then docked with the light inlet of the FC optical fiber coupler, and the fluorescent ceramic rod is docked with the light outlet of the FC optical fiber coupler by twisting the thread; the laser lighting system emits a blue laser, which enters the optical fiber through the coupler and is transmitted to the fluorescence conversion system.
[0042] As an implementation method, the laser illumination system is externally connected to a power supply; the power supply can control the generated laser power.
[0043] As an implementation mode, the external power supply is connected to the laser lighting system via a cable.
[0044] As an implementation method, the coupler couples the laser illumination system with the optical fiber, connecting the laser in the laser illumination system to the optical fiber.
[0045] As an implementation method, there is a light inlet in the fluorescence conversion system, the optical fiber is connected to the FC connector of the light inlet, the FC connector is connected to the FC fiber coupler, and the rod-shaped fluorescent ceramic is connected to the light outlet of the FC fiber coupler through a thread, and finally the laser is irradiated onto the Ce:LUAG-doped fluorescence conversion material.
[0046] The process of preparing Ce: LuAG fluorescent ceramics first involves the selection and preparation of raw materials. Usually, stable oxides are selected as the matrix, and Ce: LuAG with a doping concentration of 0-9.9% is used as the dopant. Then, the powder is prepared by solid phase reaction method, and Ce: LuAG and stable oxide powder (such as Al2O3) are ball milled to mix the raw powders evenly. Then, molding is carried out, usually by pressing, and the evenly mixed powder is poured into a cylindrical mold with a diameter of 10 cm. The formed ceramic body needs to be dried at a temperature of 80°-120° to remove moisture and prevent moisture evaporation from causing the body to dry and crack. Next, the sintering process is carried out. The powder particles are bonded together by high-temperature sintering to form a dense round rod-shaped fluorescent ceramic. The sintering temperature is generally selected between 1000°-1800°. Finally, heat treatment (1000°-1600°) and annealing (800°-1200°) are carried out after sintering to optimize the microstructure of the material and further improve the performance of the ceramic.
[0047] Group 1
[0048] Example 11
[0049] In this embodiment, CeO2, Al2O3, and Lu2O3 are first prepared to uniformly dope the rod-shaped fluorescent ceramic. When the wavelength of the incident light is about 450nm, the molar absorption coefficient of Ce-doped LuAG is 4000L·moL -1 cm -1 When the absorption coefficient is 0.8, the corresponding Ce 3+ The concentration is 0.0002mol / L. Use a high-energy ball mill to mill and add an appropriate amount of ethanol to mix with Lu2O3 and CeO2. The ball milling process is mainly to ensure that Ce 3+ The slurry after ball milling is dried at 60℃ to remove the solvent to ensure the uniformity of the powder. The dried powder is formed into a 10cm fluorescent ceramic rod by pressing or injection molding to ensure Ce 3+ Uniform doping, sintering at 1700℃ for 10h, using argon protective atmosphere to prevent Ce doping 3+ The oxidation state is affected, and finally annealing treatment is carried out at 800℃ for 4h, and finally the Ce:LuAG fluorescent ceramic rod with absorption coefficient of 0.8, quantum conversion efficiency of 0.8 and energy conversion efficiency of 0.8 is obtained. After testing, when the efficiency of incident blue light is 1w, about 64% of the blue light can be finally converted into yellow-green light to attract fish.
[0050] Example 12
[0051] In this embodiment, CeO2, Al2O3, and Lu2O3 are first prepared to uniformly dope the rod-shaped fluorescent ceramic. When the wavelength of the incident light is about 450nm, the molar absorption coefficient of Ce-doped LuAG is 3000L·moL -1 cm -1 When the absorption coefficient is 0.8, the corresponding Ce 3+ The concentration is 2.6×10 -5 mol / L, use a high-energy ball mill to mill and add an appropriate amount of ethanol to mix with Lu2O3 and CeO2. The ball milling process is mainly to ensure that Ce 3+ The slurry after ball milling is dried at 80℃ to remove the solvent to ensure the uniformity of the powder. The dried powder is formed into a 10cm fluorescent ceramic rod by pressing or injection molding to ensure Ce 3+ Uniform doping, sintering at 1600℃ for 15h, using argon protective atmosphere to prevent Ce doping 3 +The oxidation state is affected, and finally annealing treatment is carried out at 1000 ° C for 6 hours, and finally an absorption coefficient of 0.8, a quantum conversion efficiency of 0.8, and an energy conversion efficiency of 0.8 are obtained. Example 12 is selected compared with Example 11, and the molar absorption coefficient selected in Example 12 is 3000L·moL -1 cm -1 Compared with Example 11, the doping concentration has changed, but the final effect is the same. After testing, when the incident blue light efficiency is 1w, about 64% of the blue light can be finally converted into yellow-green light to attract fish.
[0052] Example 13
[0053] In this embodiment, CeO2, Al2O3, and Lu2O3 are first prepared to uniformly dope the rod-shaped fluorescent ceramics. The corresponding molar absorption coefficient is 2000 L·moL -1 cm -1 When the absorption coefficient is 0.8, the corresponding Ce 3+ The concentration is 0.0004 mol / L. Use a high-energy ball mill to mill and add an appropriate amount of ethanol to mix with Lu2O3 and CeO2. The ball milling process is mainly to ensure that Ce 3+ Doping is uniform, the milled slurry is dried at 100°C to remove the solvent to ensure the uniformity of the powder, and the dried powder is formed into a 10cm fluorescent ceramic rod by pressing or injection molding to ensure Ce 3+ Uniform doping, sintering at 1800℃ for 20h, using argon protective atmosphere to prevent Ce doping 3+ The oxidation state of the sample was affected, and finally an annealing treatment was carried out at 1200°C for 8 hours, and finally a Ce:LuAG fluorescent ceramic rod with an absorption coefficient of 0.8, a quantum conversion efficiency of 0.8, and an energy conversion efficiency of 0.8 was obtained. Compared with Example 12 and Example 11, Example 13 has a different molar absorption coefficient, Ce 3+ The doping concentration is also different, but the final effect is the same. After testing, when the incident blue light efficiency is 1w, about 64% of the blue light can be finally converted into yellow-green light to attract fish.
[0054] Group 2
[0055] Example 21
[0056] In this embodiment, CeO2, Al2O3, and Lu2O3 are first prepared to perform gradient doping on the rod-shaped fluorescent ceramic. When the wavelength of the incident light is about 450nm, the molar absorption coefficient of Ce-doped LuAG is 4000L·moL -1 cm -1, use a high-energy ball mill to mill and add an appropriate amount of acetone to mix with Lu2O3 and CeO2. The ball milling process is mainly to ensure that Ce 3+ Doping is uniform. The fired ceramic rod is divided into five equal parts. Each part absorbs 1 / 5 of the total light intensity to achieve uniform luminescence. The absorption coefficient of each part is different. When the quantum conversion efficiency is 0.8, the energy conversion efficiency is also 0.8, and the incident light intensity is 1w, the absorption coefficient of the first section is about 0.11cm -1 , according to the concentration formula, Ce 3+ The doping concentration is 2.75×10 -5 mol / L, the absorption coefficient of the second stage is about 0.14cm -1 According to the concentration formula, Ce 3+ The doping concentration is 3.5×10 - 5 mol / L, the absorption coefficient of the third section is about 0.202cm -1 According to the concentration formula, Ce 3+ The doping concentration is 5.05×10 - 5 mol / L, the absorption coefficient of the fourth section is about 0.346cm -1 According to the concentration formula, Ce 3+ The doping concentration is 8.65×10 - 5 mol / L, the absorption coefficient of the fifth section is about 0.69cm -1 According to the concentration formula, the corresponding Ce 3+ The doping concentration is 1.725×10 -4 mol / L, the ball-milled slurry is dried at 60°C to remove the solvent to ensure the uniformity of the powder, and the powders with different doping concentrations are pressed or injected together to form five sections (each section is about 2 cm) of 10 cm long rod-shaped fluorescent ceramics with different absorption coefficients, and finally sintered at 1700°C for 12 hours, and finally annealed at 800°C for 4 hours to finally form gradient-doped fluorescent ceramic rods. At this time, uniform luminescence can be achieved, but according to Lambert-Beer's law, the length of the ceramic rod cannot reach infinity, and the total absorption intensity of the fluorescent ceramic rod reaches 95%, that is, the fifth section absorbs 15% of the total light intensity, and the corresponding absorption coefficient is about 0.69cm -1 After testing, when the incident blue light efficiency is 1w, about 95% of the blue light can be finally converted into yellow-green light to attract fish.
[0057] Example 22
[0058] In this embodiment, CeO2, Al2O3, and Lu2O3 are first prepared to perform gradient doping on the rod-shaped fluorescent ceramic. When the wavelength of the incident light is about 450nm, the molar absorption coefficient of Ce-doped LuAG is 2000L·moL -1 cm -1 , use a high-energy ball mill to mill and add an appropriate amount of acetone to mix with Lu2O3 and CeO2. The ball milling process is mainly to ensure that Ce 3+ Doping is uniform. The fired ceramic rod is divided into five equal parts. Each part absorbs 1 / 5 of the total light intensity to achieve uniform luminescence. The absorption coefficient of each part is different. When the quantum conversion efficiency is 0.8, the energy conversion efficiency is also 0.8, and the incident light intensity is 1w, the absorption coefficient of the first section is about 0.11cm -1 , according to the concentration formula, Ce 3+ The doping concentration is 5.5×10 - 5 mol / L, the absorption coefficient of the second stage is about 0.14cm -1 According to the concentration formula, Ce 3+ The doping concentration is 7.0×10 -5 mol / L, the absorption coefficient of the third section is about 0.202cm -1 According to the concentration formula, Ce 3+ The doping concentration is 1.01×10 -4 mol / L, the absorption coefficient of the fourth section is about 0.346cm -1 According to the concentration formula, Ce 3+ The doping concentration is 1.73×10 -4 mol / L, the absorption coefficient of the fifth section is about 0.69cm -1 According to the concentration formula, the corresponding Ce 3+ The doping concentration is 3.45×10 -4 mol / L, the ball-milled slurry is dried at 100°C to remove the solvent to ensure the uniformity of the powder, and the powders with different doping concentrations are pressed or injected together to form five sections (each section is about 2 cm) of 10 cm long rod-shaped fluorescent ceramics with different absorption coefficients, and finally sintered at 1800°C for 20 hours, and finally annealed at 1200°C for 8 hours to finally form gradient-doped fluorescent ceramic rods. At this time, uniform luminescence can be achieved, but according to Lambert-Beer's law, the length of the ceramic rod cannot reach infinity, and the total absorption intensity of the fluorescent ceramic rod reaches 95%, that is, the fifth section absorbs 15% of the total light intensity, and the corresponding absorption coefficient is about 0.69cm -1 Compared with Example 21, the molar absorption coefficient of the ceramic shank is 4000L·moL -1 cm -1At this time, the concentration of each section is different from that of Example 21, but the final effect is the same as that of Example 21. After testing, when the incident blue light efficiency is 1w, about 95% of the blue light can be finally converted into yellow-green light to attract fish.
[0059] Example 23
[0060] In this embodiment, CeO2, Al2O3, and Lu2O3 are first prepared to perform gradient doping on the rod-shaped fluorescent ceramic. When the wavelength of the incident light is about 450nm, the molar absorption coefficient of Ce-doped LuAG is 3000L·moL -1 cm -1 , use a high-energy ball mill to mill and add an appropriate amount of acetone to mix with Lu2O3 and CeO2. The ball milling process is mainly to ensure that Ce 3+ Doping is uniform. The fired ceramic rod is divided into five equal parts. Each part absorbs 1 / 5 of the total light intensity to achieve uniform luminescence. The absorption coefficient of each part is different. When the quantum conversion efficiency is 0.8, the energy conversion efficiency is also 0.8, and the incident light intensity is 1w, the absorption coefficient of the first section is about 0.11cm -1 , according to the concentration formula, Ce 3+ The doping concentration is 3.5×10 - 5 mol / L, the absorption coefficient of the second stage is about 0.14cm -1 According to the concentration formula, Ce 3+ The doping concentration is 5.0×10 -5 mol / L, the absorption coefficient of the third section is about 0.202cm -1 According to the concentration formula, Ce 3+ The concentration range is 6.7×10 -5 mol / L, the absorption coefficient of the fourth section is about 0.346cm -1 According to the concentration formula, Ce 3+ The concentration range is 1.1.15×10 -4 mol / L, the absorption coefficient of the fifth section is about 0.69cm -1 According to the concentration formula, the corresponding Ce 3+ The concentration range is 2.3×10 -4mol / L, the ball-milled slurry is dried at 80°C to remove the solvent to ensure the uniformity of the powder, and the powders with different doping concentrations are pressed or injected together to form five sections (each section is about 2 cm) of 10 cm long rod-shaped fluorescent ceramics with different absorption coefficients, and finally sintered at 1750°C for 16 hours, and finally annealed at 1000°C for 6 hours to finally form gradient-doped fluorescent ceramic rods. At this time, uniform luminescence can be achieved, but according to Lambert-Beer's law, the length of the ceramic rod cannot reach infinity, and the total absorption intensity of the fluorescent ceramic rod reaches 95%, that is, the fifth section absorbs 15% of the total light intensity, and the corresponding absorption coefficient is about 0.69 cm -1 Compared with Examples 21 and 22, the molar absorption coefficient selected in Example 23 is 3000 L·moL -1 cm -1 At this time, the concentration of each section is different from that of Examples 21 and 22, but the final effect is the same. After testing, when the incident blue light efficiency is 1w, about 95% of the blue light can be finally converted into yellow-green light to attract fish.
[0061] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0062] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A fish attracting lamp system, comprising a laser light source and a matching optical fiber system for transmitting laser light, characterized in that: It also includes a fluorescence conversion system for receiving blue laser, and the fluorescence conversion system includes: a fluorescent ceramic structure arranged away from the laser light source, which is used to emit yellow-green light after receiving laser irradiation.
2. The fish attracting light system according to claim 1, characterized in that: The fluorescent ceramic structure includes a main structure of Ce:LuAG fluorescent ceramic.
3. The fish attracting light system according to claim 2, characterized in that: Ce in the Ce:LuAG fluorescent ceramic 3+ The doping amount is 0-9.9wt.%.
4. The fish attracting lamp system according to claim 3, characterized in that: The main structure includes a cylindrical thread structure or an inclined cross-section thread structure.
5. The fish attracting light system according to claim 3, characterized in that: The doping of Ce:LuAG in the Ce:LuAG fluorescent ceramic is uniform doping or gradient doping.
6. The fish attracting light system according to any one of claims 2-3, characterized in that: The Ce:LuAG fluorescent ceramic is obtained by mixing Ce:LuAG as a dopant with oxide powder, pressing and forming, and then drying and sintering.
7. The fish attracting lamp system according to claim 6, characterized in that: The oxide powder is selected from aluminum oxide powder, lutetium oxide powder, and cerium oxide powder.
8. The fish attracting lamp system according to claim 6, characterized in that: The sintering is performed at a temperature between 1000° and 1800° and a sintering time of 10 to 20 hours.
9. Fishing device comprising the fish attracting light system according to any one of claims 1-8.